1994
DOI: 10.1159/000247122
|View full text |Cite
|
Sign up to set email alerts
|

Confluent and Reticulated Papillomatosis: A Case with Concurrent Acanthosis nigricans Associated with Obesity and Insulin Resistance

Abstract: A 19-year-old Japanese man with confluent and reticulated papillomatosis (CRP) is presented. He was an obese and dark-complexioned man, who had impaired glucose tolerance and hyperinsulinemia. The clinical and histological findings were consistent with the diagnosis of CRP. He also had acanthosis nigricans (AN) on his axillae and nape. Neither spores nor hyphae were detected from scales; antifungal treatment had no benefit. Although the reduction of his weight was unsuccessful, oral etretinate therapy resulted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
3

Year Published

1995
1995
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 10 publications
0
22
0
3
Order By: Relevance
“…However, a close relationship between the two is suggested by similar predisposing characteristics including young age, obese, dark-skinned persons and parallel response to weight reduction or etretinate therapy 5,6 . A pathogenetic link between the two conditions is suggested by insulin resistance and consequent hyperinsulinemia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a close relationship between the two is suggested by similar predisposing characteristics including young age, obese, dark-skinned persons and parallel response to weight reduction or etretinate therapy 5,6 . A pathogenetic link between the two conditions is suggested by insulin resistance and consequent hyperinsulinemia.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of underlying endocrinopathies may explain the concurrent CRP and AN in our patients. There have been only two prior reports of concurrent CRP and AN reported in the medical literature 5,6 . However the coexistence of the two diseases is not rare.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, an abnormal host reaction to Pityrosporum orbiculare infection has been discussed [14,15] . Other investigators have reported an association between confluent and reticulated papillomatosis and acanthosis nigricans [19,20] . As the 2 disorders are identical under the microscope and sometimes overlap clinically, there is an ongoing debate as to whether or not they are one and the same disease.…”
Section: Discussionmentioning
confidence: 99%
“…The eti ology is unknown; however, an association with Pityrosporum infection |1, 2], thyroid disease |11, Cushing's syndrome |l |, acantho sis nigricans, impaired glucose tolerance or hyperinsulinemia |2) has been suggested. Also, there is evidence that CRP could be due to 'a genetically determined keratinization defect' [2], Treatment includes retinoids, sele nium sulfide, ketoconazole, erythromycin and tetracycline [1,2].…”
Section: Confluent and Reticulated Papillomatosis: Response To Topicamentioning
confidence: 99%
“…skin and soft tissue and genitourinary system [1][2][3][4][5]. The major adverse effects include nausea, abdominal pain and diarrhea.…”
Section: Nail Pigmentation Due To Roxithromycinmentioning
confidence: 99%